Relationship between corporate governance, voluntary disclosure and cost of equity : evidence from Singapore. - Chan, Eileen Sok Leen. (2008)
This study examines the effects of voluntary disclosure and corporate governance on the cost of equity capital using a sample size of 164 companies listed on Singapore Stock Exchange Mainboard. In addition, we consider the effects of disclosing forward-looking statements on COE for firms engaging in external financing shortly after the release of their annual reports.